Pengembangan Wawasan Kebangsaan Melalui Media Sosial (Studi Kasus Warganet Indonesia dalam Isu yang Mengusik Nasionalisme) - Samodro, Dewanto; Satrio, Jati; Zempi, Chairun Nisa (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Indonesian citizens are individuals who actively use social media. A study showed that more than half of Indonesians used social media. Not infrequently, Indonesian netizens act in response to a number of issues that disturb the nation’s sense of nationalism. This study uses a qualitative case study method to captured how Indonesian netizens responded to a number of issues that disturb the sense of nationalism, as well as provide an illustration that netizens’ activities in Indonesia are a potential in developing national insight through social media.